An Analysis of Code-Mixing and Code-Switching in EFL Teaching of Cross Cultural Communication Context - Kustati, Martin (AT-TALIM, 2014)
The objective of the paper is to determine types of code-mixing and code-switching made by teachers and students in EFL cross cultural communication class and to identify reasons for the emergence of code-switching and mixing in the classroom. The data was obtained through observation and in-depth interviews of the second year students of undergraduate program of English in Tarbiyah Faculty, IAIN IB Padang. The finding showed that tag-switching, intra-sentential, inter-sentential, and intra-word were commonly used by EFL teachers and students in classroom. It was also found that the teachers used code-mixing and switching in the process of clarifying certain issues to make them more comprehensible to students. Teachers also do these kinds of switching during their attempt to promote relationship with students, to switch the topic, and to persuade or motivate students to be more engaged in learning English. Meanwhile, the students mix and switch their language to overcome their lack of knowledge of English. It is expected that this study provided empirical evidence to advise on their optimal uses in EFL teaching of State Institute for Islamic Studies.Copyright Â© 2014 by Al-Talim All right reserved